INTEGRATED LINKAGES TO THE SUSTAINABILITY OF DINOYO CERAMIC VILLAGE, MALANG - Efani, Anthon; Manzilati, Asfi; Bakar, Abu (Journal of Indonesian Applied Economics, 2021)
Dinoyo is a ceramic handicraft center in Malang City. The cultural potential of the Dinoyo people, especially ceramic craftsmen, which has survived to this day is one of the fulcrums for cultural preservation efforts. The purpose of this research is to create a marketing strategy, to improve the sustainability of the Dinoyo Ceramic Village both in terms of production and function of the village as a center for literacy and cultural preservation in Malang City and one of them is through the optimization of promotional media to increase sales and support promotional events in Dinoyo Ceramic Village. The method used in this research is descriptive qualitative structured interviews. The results showed that the dinoyo ceramic village had not made good use of the marketing strategy so that it needed optimization of online media partnerships and the use of online social media. Thus this research contributes to increasing the competitiveness of dinoyo ceramics in order to improve community welfare.